Comparison of Antibacterial Activity of Ethanol Extract and Nanoparticles of Crassocephallum Crepidioides S.Moore Against Staphylococcus Aureus - Candrika, Candrika; Dalimunthe, Aminah; Bangun, Hakim (Newinera Publisher, 2024)
This research seeks to examine the width of the inhibitory zone of extracts and nanoparticles of Crassocephalum crepidioides leaf simplisia, which have many advantages such as wound therapy, diarrhea relief, anti-inflammatory properties, and antibacterial effects. The antibacterial activity of Crassochepallum crepidioides (Benth) was evaluated by using the ethanol extract and nanoparticles. S. Moore departs. The agar diffusion technique was used to test it on paper plates. 0.1 ml of bacterial inoculum was introduced into a sterile petri dish, followed by the addition of 15 ml of Mueller Hinton agar media at a temperature range of 45-50ºC. Subsequently, multiple paper plates were immersed in a test solution containing a strong leaf ethanol extract and nanoparticles with different concentrations. Characterization reveals that Crassocephalum crepidioides is composed of many bioactive components, including alkaloids, flavonoids, saponins, tannins, and steroids. The analysis of the extract revealed that it contained 5.92% water, 12.86% total ash, 1.55% acid-insoluble ash, 14.33% water-soluble essence, and 9.34% ethanol-soluble essence. The nanoparticles had a size of 64.37 nm and exhibited antibacterial activity of extract ethanol at a concentration of 50% with a diameter of 12,00 mm. The minor concentration of the extract had a diameter of 3,166 mm, while the nanoparticles showed antibacterial activity at a concentration of 50% with a diameter of 10,53 mm. The minor concentration of the nanoparticle had a diameter of 3,00 mm The activity test results of the ethanol extract of Crassochepallum crepidioides with nanoparticles demonstrated that the inhibitory diameter of the ethanol extraction results remained more strong compared to the nanoparticles of simplisia powder.